(untitled) (Journal of Parents and Teachers, 2013)
The article’s main objective is to carry out workshops of language stimulation in infant education. These workshops must be prepared in a properly way in order to establish the classroom’s speaking level as well as to detect any altered or poor developed aspect. There are lots of resources for stimulating the language such as games and activities, where children are able to participate and therefore workshop’s contents are worked. It is also very important the use of tools as smart board in this kind of workshops. Parent’s role is essential in this speaking process, and for this reason the author provides them some patterns to reinforce the work carried out at school.